Multi-actor approaches to implement cooperative strategies and value chains based on sustainability - Caterina Contini; Giuseppe Marotta; Biancamaria Torquati (Agricultural and Food Economics, 2020)
This special issue of Agricultural and Food Economics consists of four articles that were part of the scientific programme of the First SIDEA-SIEA Joint Conference, held in Bisceglie in September 2017. The conference afforded agricultural economists the opportunity to reflect on cooperative strategies to promote competitiveness of the agri-food supply chain, with a focus on environmental quality and social sustainability. The selected articles address these themes from different perspectives: those of firms, of consumers, and of policy makers, stressing that sustainability calls for the active participation of all of the actors. The case studies presented propose an effective interpretation of the strategies for value creation with respect to the challenges of climate change, food waste management, the development of marginal rural areas, and that of the fish sector.
Keywords: 330